Digital Trends and 21st Century Competencies in Educational Transformation - Ismuni, Mutdi; Usman, M.; Choiriyah, Siti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This article explores digital trends impacting the educational process and the importance of integrating 21st century competencies within today's educational environment. With the introduction of technology into learning, online education has become a norm, allowing broader access to education. Digital learning platforms and educational apps have become integral parts of the curriculum, offering possibilities for students to learn independently and collaboratively. The importance of 21st century competencies such as critical thinking, creativity, collaboration, and digital literacy is increasingly evident in education. Developing these skills is seen as essential preparation for students to succeed in a rapidly changing world. However, educational transformation is not just about adapting the curriculum; it also involves teacher training and close collaboration between educational institutions and the industry. The article highlights the importance of constant adaptation in education to meet the demands of the times. Aligning curricula with current needs, providing necessary training for educators, and fostering collaboration with the industry sector are crucial steps in ensuring that education equips future generations with relevant skills. Through the integration of digital trends and 21st century competencies, education can become a strong foundation for individual progress and success in facing increasingly complex challenges in today's global era.